The Selective HDAC6 Inhibitor ACY-738 Impacts Memory and Disease Regulation in an Animal Model of Multiple Sclerosis - LoPresti, Patrizia (Frontiers in Neurology, 2019)
Multiple sclerosis (MS) is a complex disease characterized by autoimmune demyelination and progressive neurodegeneration. Pathogenetic mechanisms of the disease remain largely unknown. Changes in synaptic functions have been reported; however, the significance of such alterations in the disease course remains unclear. Furthermore, the therapeutic potential of targeting synapses is not well-established. Synapses have key signaling elements that regulate intracellular transport and overall neuronal health. Histone deacetylase (HDAC)6 is a microtubule-associated deacetylase. The interaction between HDAC6 and microtubules is augmented by HDAC6 inhibitors. In this study, experimental autoimmune encephalomyelitis (EAE) mice, an animal model of MS, were treated with the HDAC6 inhibitor drug ACY-738 (20 mg/kg) on day 9 and day 10 post-immunization. Mice were assessed for working memory using the cross-maze test at 10 days post-immunization (d.p.i.), whereas disease scores were recorded over approximately 4 weeks post-immunization. We observed that ACY-738 delayed disease onset and reduced disease severity. Most importantly, ACY-738 increased short-term memory in a manner sensitive to disease severity. We induced EAE disease with various amounts of myelin oligodendrocyte glycoprotein (MOG35-55). EAE mice receiving 100 μg of MOG35-55 and treated with ACY-738 had a statistically significant increase in short term-memory compared to naive mice. Additionally, EAE mice receiving 50 μg MOG35-55 and treated with ACY-738 had a statistically significant increase in short term-memory when compared to EAE mice without drug treatment. In contrast, ACY-738 did not change short-term memory in EAE mice immunized with 200 μg of MOG35-55. Because ACY-738 increases short-term memory only with lower amounts of EAE-inducing reagents, we hypothesize that the inflammatory-demyelinating environment induced by higher amount of EAE-inducing reagents overpowers (at day 10 post-immunization) the synaptic molecules targeted by ACY-738. These studies pave the way for developing ACY-738-like compounds for MS patients and for using ACY-738 as a probe to elucidate disease-sensitive changes at the synapses occurring early in the disease course.